2018
DOI: 10.1186/s12903-018-0611-6
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effect of a diode laser on Enterococcus faecalis in human primary teeth—an in vitro study

Abstract: BackgroundIn recent years, the diode laser (810 nm) has been used for root canal disinfection, which plays an important role in endodontic therapy. This study was undertaken to evaluate the disinfecting ability of a diode laser in experimentally infected root canals of primary teeth.MethodsHuman retained mandibular primary anterior teeth without apical foramen resorption were selected and contaminated with Enterococcus faecalis for 21 days. The specimens were randomly divided into four groups: the negative gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
1
17
0
4
Order By: Relevance
“…Previous studies on the antimicrobial effects of diode laser irradiation were mainly conducted in medicine and were focused on pathogenic bacteria such as Enterococcus faecalis and Escherichia coli. Nevertheless, higher values of average laser power than in this paper were most often applied (Beer et al, 2011;Asnaashari et al, 2016;Olivi et al, 2016;Dai et al, 2018), with similar ones applied less often (Tosun et al, 2012;Sadık et al, 2013).…”
Section: Discussionmentioning
confidence: 45%
“…Previous studies on the antimicrobial effects of diode laser irradiation were mainly conducted in medicine and were focused on pathogenic bacteria such as Enterococcus faecalis and Escherichia coli. Nevertheless, higher values of average laser power than in this paper were most often applied (Beer et al, 2011;Asnaashari et al, 2016;Olivi et al, 2016;Dai et al, 2018), with similar ones applied less often (Tosun et al, 2012;Sadık et al, 2013).…”
Section: Discussionmentioning
confidence: 45%
“…The diode laser uses the solid semiconductor of aluminum gallium arsenide as an active medium operating in the near-infrared spectral region, between 808 and 980 nm. 35,36 The penetration of diode laser irradiation to a depth of up to 1000 μm into dentinal tubules could be responsible for its strong bactericidal effect. On the other hand, chemical disinfectants can only reach up to 100 μm into the surrounding dentinal tubules, whereas the bacteria can penetrate and remain protected over 1000 μm in the deeper layers of dentin.…”
Section: Discussionmentioning
confidence: 99%
“…can cause irreversible injury to the periodontal tissues. 36 Gutknecht et al demonstrated that diode laser irradiation for 5 seconds, with 10 seconds of resting time, should be considered to avoid a temperature rise to an undesired level. 39 Schoop et al also drew similar conclusions that a diode laser showed the lowest temperature increases compared with other laser devices and was suitable for the disinfection of root canals.…”
Section: Discussionmentioning
confidence: 99%
“…2 Numerous previous studies have been conducted to evaluate the bactericidal effect of various wavelengths of lasers, but most of these studies were conducted on dentine slices of 100, 300, 500, and 1000 μm. [5][6][7] They were conducted with dentine samples up to 1000 μm, therefore limiting our understanding as to the effects of lasers and biocides, with one study beyond 2000 μm. 8 This in vitro study aimed to compare the photobiomodulation effect of a 940 nm laser on Enterococcus faecalis through varying thicknesses of human root dentin slices.…”
Section: Introductionmentioning
confidence: 99%